Anticancer flavonoids producing endophytic fungi: A review - Kirti G. Sahu; Deepak S. Khobragade; Shriniwas P. Patil (Journal of Holistic Integrative Pharmacy)
Plants living in different environments inhabit endophytic microbes. The relationship between plants and endophytic microbes may be symbiotic or parasitic. Transmission of endophytes varies when they are obtained through roots or cracks on bark or airborne spores from soil or originated from seeds or pollens. Endophytes could be bacteria or fungi. So far, actual flavonoids have been detected from endophytic fungi only. Several flavonoids like rutin, quercetin, kaempferol, naringenin, vitexin, apigenin, luteolin, chrysin, and silymarin are isolated from endophytic fungi. These flavonoids are tested for their anticancer activity on different cell lines and their mechanisms were determined. This review focuses on endophytic fungi from which anticancer flavonoids have been reported.